Application of fractional part in expansion

Algebra Level 5

( a + b c ) n = I + f \displaystyle (a+b\sqrt c)^{n}= I+f where I \displaystyle I is integer part and f \displaystyle f is fractional part..

Which of the following are true if a 2 1 = b 2 c \displaystyle a^{2}-1=b^{2}c

  1. Value of 1 f \displaystyle 1-f is I \displaystyle I

  2. Value of 1 f \displaystyle 1-f is 1 I \displaystyle \frac { 1 }{ I }

  3. Expansion of ( a b c ) n \displaystyle (a-b\sqrt c)^{n} is 1 f \displaystyle 1-f .

  4. Value of 1 + f \displaystyle 1+f is I \displaystyle I

  5. Value of 1 + f \displaystyle 1+f is 1 I \displaystyle \frac { 1 }{ I }

  6. Expansion of ( a b c ) n \displaystyle (a-b\sqrt c)^{n} is 1 + f \displaystyle 1+f .

  7. 1 1 f f = I \displaystyle \frac{1}{1-f}-f=I

  8. 1 1 + f f = I \displaystyle \frac{1}{1+f}-f=I

Submit the answer as the product of the true statements.

For example if 2,3,5 are true submit the answer as 30

0 < a b c < 1 \displaystyle 0 <a-b\sqrt c<1 , n is a positive integer. a>1, c>0


The answer is 21.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Prince Loomba
Apr 19, 2016

( a + b c ) n = (a+b\sqrt{c})^{n}= ( n 0 ) n \choose 0 a n a^{n} + ( n 1 ) n \choose 1 a n 1 × b c 1 a^{n-1} \times b\sqrt c^{1} +......... =I+f (fractional part)
( a b c ) n = (a-b\sqrt{c})^{n}= ( n 0 ) n \choose 0 a n a^{n} - ( n 1 ) n \choose 1 a n 1 × b c 1 a^{n-1} \times b\sqrt c^{1} +......... =p+g (fractional part)
Adding, ( a + b c ) n (a+b\sqrt{c})^{n} + ( a b c ) n (a-b\sqrt{c})^{n} = all integer terms (irrational terms cancelled). Note that ( a b c ) < 1 (a-b\sqrt{c})<1 . Thus all powers are less than 1 or p = 0 p=0 ................... ............................................. I+f+g=integer, I is integer. Thus f+g is integer. 0 < f + g < 2 0<f+g<2 implies that f+g =1 or g = 1 f g=1-f .............................................. Since a 2 b 2 c = 1 a^{2}-b^{2}c=1 it is clear that ( a + b c ) n (a+b\sqrt{c})^{n} X ( a b c ) n (a-b\sqrt{c})^{n} =1............................................................ ( I + f ) × g = 1 (I+f) \times g=1 or ( I + f ) × ( 1 f ) = 1 (I+f) \times (1-f)=1 or 1 1 f f = I \frac{1}{1-f}-f=I ................................................................................................ Thus 3 and 7 are true. Answer =21

Following corrections must be made to the problem to make it clear and appropriate :-

● First of all, specify that 0 < a b c < 1 0\,<\,a- b\sqrt c \,<\,1 .

● Note that, you've mentioned a b c < 1 a-b\sqrt{c}\,<\,1 which more or less indicates that n n is a positive number, but, you need to specify n ϵ Z + n \,\epsilon\ \mathbb{Z^{+}} so that the possibility of n n being a non - intgeral positive real number gets ruled out.

Notice that, we can't say anything about a + b c a+b\sqrt c , in case n n is a non - integral positive real number.

c > 0 c\,>0 and a > 1 a>1 .

Notice that, we've special cases where your reasoning works, they're:-

c = 0 , a 1 c=0,a≠1 and b = c = 0 , a 1 b=c=0,a≠1 .

Aditya Sky - 5 years ago

Log in to reply

Any more corrections?

Prince Loomba - 5 years ago

Log in to reply

Naa. I don't think so.

Aditya Sky - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...